Flow Investigation Inside the Vacuum Gripper for Labeling Application with Dimensions of 100 mm × 100 mm Using the CFD Method - Eric Budiono Setiawan; Agus Halim; Steven Darmawan; Didi Widya Utama; Kevin Raynaldo (Jurnal Asiimetrik: Jurnal Ilmiah Rekayasa Dan Inovasi, 2024)
Nowadays, the application of automation in the manufacturing sector is important to increase production efficiency. One of the variations in industrial automation is the vacuum gripper. Vacuum grippers are specifically designed to handle specific workpieces, such as labeling application. Label characteristics that easily bend and stick to the workpiece when peeled off require a specific gripper. This research was carried out using 2 methods, experimental method and CFD simulation method. The experimental method was carried out by collecting pressure data with Arduino. Data from this experiment will be used for the CFD simulation. Based on these experimental tests, the average vacuum pressure obtained was -44.372 kPa. From the simulation vacuum pressure on the 12 inlet holes was obtained. The largest vacuum pressure was at inlet 12 with a vacuum pressure value of -44372.11 Pa, while the smallest was at inlet hole 1 with a value of -44371.86 Pa. The pressure distribution is evenly distributed at all the suction point and has suited the design requirements.